Training of professionals in information: Virtual Education in Central - Chacón Alvarado, Lucía (2000)
Education is a priority area in developing countries and training and human resource training strengthens economic and intellectual productivity and should become an important transmitter of knowledge. The revolution that has occurred in the field of information and technology has led to the need for a new professional possessing the appropriate skills to enable it to cope with these changes safely and efficiently.The School of Library, Documentation and Information of the National University in Costa Rica, within its prospective vision poses to extend its curriculum to Central America. With the facilities offered by telecommunications networks and information technology aims to provide an educational option in the training of information professionals through virtual education. This is a proposal for formal and continuing education will help develop librarianship in this region.